Farming practices and Roller Coracias garrulus conservation in south-west Spain - Aviles, J M; Parejo, D (BIRD CONSERVATION INTERNATIONAL, 2004)
There are no previous studies supporting the link between the decline of Roller Coracias garrulus populations in the Palaearctic and agricultural intensification. We studied the effect of farming practices on Roller reproduction during 1988-1991 in south-west Spain. Nest-boxes were installed on power pylons that crossed six different man-made habitats representing the most characteristic habitats in the Mediterranean region: pasture fields with and without holm oak Quercus roffindifolia trees, cereal fields with and without holm oak trees, scrub fields and irrigated fields. Rollers nesting in nest-boxes erected in unwooded pasture field had the highest breeding success, suggesting that this is the most suitable nesting habitat of Rollers in the region. There were no significant effects of farming practices in habitat adjacent to nests on Roller laying date and clutch size. However, after controlling for laying date, current agricultural practices around nests affected chick mortality, with higher losses in irrigated fields. Breeding success and egg productivity were also affected by farming activities, with the lowest values in irrigated fields. Future conservation plans for Rollers should consider that nest-box provision might increase habitat suitability for Roller reproduction and that highly intensified agricultural practices might have deleterious effects on Roller populations.
APS
Keywords: Agricultural intensification; farming practices; Mediterranean; nest-boxes; reproduction; Roller Coracias garrulus

Farming practices and Roller Coracias garrulus conservation in south-west Spain - Aviles, J. M.; Parejo, D. (BIRD CONSERVATION INTERNATIONAL, 2004)
There are no previous studies supporting the link between the decline of Roller Coracias garrulus populations in the Palaearctic and agricultural intensification. We studied the effect of farming practices on Roller reproduction during 1988-1991 in south-west Spain. Nest-boxes were installed on power pylons that crossed six different man-made habitats representing the most characteristic habitats in the Mediterranean region: pasture fields with and without holm oak Quercus roffindifolia trees, cereal fields with and without holm oak trees, scrub fields and irrigated fields. Rollers nesting in nest-boxes erected in unwooded pasture field had the highest breeding success, suggesting that this is the most suitable nesting habitat of Rollers in the region. There were no significant effects of farming practices in habitat adjacent to nests on Roller laying date and clutch size. However, after controlling for laying date, current agricultural practices around nests affected chick mortality, with higher losses in irrigated fields. Breeding success and egg productivity were also affected by farming activities, with the lowest values in irrigated fields. Future conservation plans for Rollers should consider that nest-box provision might increase habitat suitability for Roller reproduction and that highly intensified agricultural practices might have deleterious effects on Roller populations.
APSAPSThe following values have no corresponding Zotero field: pub-location: 40 WEST 20TH ST, NEW YORK, NY 10011-4211 USA publisher: CAMBRIDGE UNIV PRESS
Keywords: Agricultural intensification; farming practices; Mediterranean; nest-boxes; reproduction; Roller Coracias garrulus

BREEDING ECOLOGY OF THE BLUE TIT PARUS-CAERULEUS IN EASTERN SPAIN - A COMPARISON WITH OTHER LOCALITIES WITH SPECIAL REFERENCE TO CORSICA - GILDELGADO, J A; López, G; BARBA, E (ORNIS SCANDINAVICA, 1992)
Aspects of the breeding ecology of the Blue Tit Parus caeruleus were studied in intermediate stages of succession in a holm oak forest at Monte Poblet (eastern Spain) from 1985 to 1991. In different years the density in two plots without nest-boxes varied between 1.0 and 6.5 pairs per 10 ha. Nestbox introduction seems to have increased the density of breeding pairs. The mean laying date was earlier (6 vs. 13 May) in low altitude (500-750 m a.s.l.) plots than in a high altitude (900-1000) m a.s.l.) plot, but clutch size (6.9 vs. 6.5 eggs) was not significantly different (mean 6.6 eggs). No differences in mean laying dates were found between years. Significant differences in clutch size were found only between two years at the high altitude site. There was a slight, non-significant, seasonal decline in clutch size. No second clutches were laid. These results are discussed in the context of other Mediterranean studies with special focus on the differences and similarities between Corsican and mainland populations. It is shown that most of the characteristics of the Corsican population (i.e. density, habitat use, laying date, clutch size, number of broods per year) are shared by some populations on the mainland. On the other hand, some breeding traits of Blue Tit populations in southern France are closer to those of Central and North European populations than to the Iberian ones.
APS
Keywords: Blue tit; breeding ecology; Holm oak forest; nest-boxes; Parus cearuleus; Spain; succession stages

THE IMPORTANCE OF TERRITORIAL BEHAVIOR AMONG BLUE TITS (PARUS-CAERULEUS) BREEDING IN A HOLM OAK FOREST - Clamens, A. (Revue D Ecologie-La Terre Et La Vie, 1987)
In a ringed population of Blue Tits (Parus caeruleus) living in a Holm Oak (Quercus ilex) forest of Languedoc, Southern France, and provided with artificial nest-boxes, territorial behaviour plays a major role in limiting the number of breeding pairs. The experimental removal, or the spontaneous disappearance, of a breeding pair is followed by an increase in size of the territories of the neigbouring pairs, or by the arrival of non-ringed juvenile individuals settling in the vacant territory. In a Holm Oak forest without artificial nest-boxes, territorial behaviour does not play such a role, as the major limiting factor in that case is the number of available tree-holes. Pairs of Blue Tits settled on territories where Downy Oaks (Quercus pubescens) are mixed with Holm Oaks, lay their eggs four days earlier on the average, than Blue Tits breeding in pure Holm Oak forest. However, the number of fledglings per brood, and their body weight at 15 days of age, tend to be smaller. The benefit of a later laying date in pure Holm Oak forest quite likely lies in a better synchronization of the maximum nutritional requirements of the young, and of the period of maximum food availability in the environment.
APSAPSThe following values have no corresponding Zotero field: label: Biodiversidade
Keywords: Biodiversidade; breeding pairs; France; holm oak forests; nest-boxes; Parus caeruleus; Quercus ilex